Spatial monitoring of natural resource condition in Southern Africa - Van der Merwe, Joseph Petrus Albertus (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Geography and Environmental Studies))--University of Stellenbosch, 2005.